Selbstverständlich - und doch umstritten Wie sich Organisationen bezüglich Gleichstellung legitimieren - Nussbaumer, Melanie (Gender Issues, 2023)
This study focuses on the relationship between organizations and society in the field of gender equality in Switzerland. The empirical research examines how companies and nonprofit organizations deal with the concern of gender equality and describes which societal discourses are included in organizational logics. The analysis shows which gender equality goals are perceived as legitimate and how they are presented as obvious in a first step. Organizations fundamentally support the gender equality cause in order to also answer to a perceived societal expectation. The controversial nature of the issue comes to the fore when the measures to achieve the goal are discussed in more concrete terms. Thereby, the problem analysis of existing gender inequalities is often not conducted. As Melanie Nussbaumer argues in the study, an understanding of structural inequalities would be necessary in order to be able to take targeted measures to achieve gender equality.